Do student initial expectations about PBL match their final perceptions? - Fernandes, Sandra (2020)
This paper presents findings from a PBL approach which takes place in the Integrated Master's degree of Industrial Engineering and Management (IEM), at the University of Minho, Portugal. It is part of a curricular unit in the 1st year of the 1st semester called Integrated Project of Industrial Engineering and Management 1 (IPIEM1). This curricular unit follows PBL approach. In total, 56 students participated in the PBL approach in the academic year 2019/2020, forming six teams of nine to ten students. This paper aims to analyse students´ initial expectations about PBL and compare them with their final perceptions concerning their experience. Data were collected from an online survey, applied at the beginning of the project (n=41), in the 1st week, and at the end of the project (n=33), in the last week. This survey has been used successfully, since the year 2008/2009, to evaluate PBL approaches from students' point of view. In 2019/2020, the survey was adapted to be used for the first time, also at the start of the project, to collect students' initial expectations. Authors understand that the first week of the project is very intense and demanding, as students become aware of the several challenges which they will face throughout the semester. Findings form the comparative analysis of the survey show that teamwork appears as one of the most positive aspects about the PBL experience, but also one of the most challenging issues for students to overcome. Beyond the “normal” students' concerns about teamwork, high workload, and other issues, the second survey revealed interesting insights from students in regard to their understanding of the PBL assessment model, that were not perceived in the first week. Qualitative data from findings will also be explored and discussed in the paper.